Polyformaldehyde modified material and preparation method thereof

By adding components such as copolyformaldehyde resin, thermoplastic polyurethane and inorganic nanomaterials to the polyformaldehyde material, high-speed mixing and twin-screw extruder are used for melt blending to form core-shell structural particles, solving the problems of low impact toughness and mechanical strength of POM materials, significantly improving the toughness and rigidity of the material, and achieving the effect of balanced performance.

CN119552476APending Publication Date: 2025-03-04TIANJIN BOHUA YONGLI CHEM IND

Patent Information

Application Number
CN202411743601.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-10-31
Filing Date
2024-11-30
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The low impact toughness and mechanical strength of polyformaldehyde (POM) materials lead to easy decomposition during processing, limiting their further application in various fields.

Method used

A polyformaldehyde modified material, including copolyformaldehyde resin, thermoplastic polyurethane, inorganic nanomaterial, formaldehyde absorber, antioxidant, compatible agent, lubricant and other components, is melt blended through high-speed mixing and a twin-screw extruder to form core-shell structural particles to improve toughness.

Benefits of technology

The notch impact strength and nominal strain of the POM material are significantly improved, the notch sensitivity of the material is reduced, and the rigidity and strength of the material are maintained to achieve a rigid and tough equilibrium state.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005163063440000061
    Figure BDA0005163063440000061
Patent Text Reader

Abstract

The invention discloses a polyformaldehyde modified material and a preparation method thereof. Comprising the following components in percentage by weight: 75.80 to 88.89 percent of co-polyoxymethylene resin, 9.0 to 21.3 percent of thermoplastic polyurethane, 0.89 to 1.95 percent of an inorganic nano material, 0.29 to 0.34 percent of an antioxidant, 0.13 to 0.15 percent of a lubricant, 0.10 to 0.12 percent of a formaldehyde absorbent and 0.43 to 0.68 percent of a compatilizer. The polyformaldehyde modified material is prepared by drawing, cooling, granulating and drying the materials in a twin-screw extruder through a two-step melt blending method, the notch impact strength of the polyformaldehyde modified material can reach 16.83 KJ / m < 2 >, the nominal strain at break can reach 66%, and the bending modulus can reach 1720 MPa. The polyformaldehyde modified material has good comprehensive mechanical properties, greatly improved toughness, and good and balanced other properties such as strength and rigidity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of engineering plastics, in particular to a toughened polyoxymethylene modified material and a preparation method thereof. Background Art

[0002] Polyoxymethylene (POM) is a thermoplastic engineering plastic with excellent comprehensive performance. It has the advantages of high rigidity, high hardness, wear resistance, good self-lubrication, dimensional stability, excellent fatigue resistance and creep resistance. POM has hardness, strength and rigidity similar to metals. It is one of the engineering plastics with mechanical properties closest to metal materials. It is widely used in automobiles, aerospace, machinery, electronic appliances and other fields.

[0003] Since POM is a linear polymer without side chains, it has a fast crystallization speed and high crystallinity, and is easy to form a large spherulite structure, which leads to the disadvantages of low impact toughness, high notch sensitivity, and easy decomposition during processing, which greatly limits its further application in various fields. Therefore, it is very important to improve the impact toughness of POM and improve the decomposition of POM during processing.

[0004] At present, the modification method of POM resin is mainly toughening modification to improve the impact resistance of polyoxymethylene. Commonly used elastomers for toughening polyoxymethylene include thermoplastic polyurethane (TPU), nitrile rubber (NBR), ethylene-vinyl acetate copolymer (EVA) and ethylene-octene copolymer thermoplastic elastomer (POE), etc., and the toughness of POM is improved by polymer blending and melting. CN111253708A discloses the invention of a PUR toughened and reinforced modified polyoxymethylene material. The PUR toughened and reinforced POM material can maintain its toughness, and at the same time improve the wear resistance of the POM material by alumina powder. CN1027511C discloses a method for preparing a polyurethane / polyoxymethylene composite material, in which an amorphous thermoplastic polymer is added as a third component, and the composite material has better molding shrinkage and mechanical properties.

[0005] There are neither side groups nor functional groups in the POM molecular chain. The polarity between POM molecules is very weak and the compatibility with most polymers is extremely low. If a polymer is used for toughening and modification, the compatibility between POM and the toughening agent must be improved. CN1283719C discloses a method for preparing a polyurethane toughened polyoxymethylene composition, in which maleic anhydride grafted copolymer is used to improve compatibility, and the elongation and tensile strength of the composition are significantly improved. CN1233733C discloses a method for preparing a polyoxymethylene / polyurethane blend, in which ethylene-vinyl acetate, ethylene-ethyl acrylate or ethylene-acrylic acid copolymer is added to improve compatibility, effectively improving the impact resistance and thermal stability of the composite material.

[0006] When elastomer is added in the presence of compatibilizer, the notched impact strength of POM is significantly improved, but when its toughness is greatly improved, the rigidity and strength of the material will decrease accordingly. In the prior art, rigid fillers are often used to toughen and strengthen POM, such as glass fiber, carbon fiber, talcum powder and inorganic nanomaterials. At present, the effective toughening modification of POM is still the research focus and hotspot of the polymer materials industry. Summary of the invention

[0007] The invention provides a polyoxymethylene modified material and a preparation method thereof, which solves the technical problems of low impact toughness and mechanical strength of POM and improves the processing process of POM.

[0008] The technical solution adopted by the present invention is: a polyoxymethylene modified material, comprising the following components and mass percentage contents:

[0009] Acetal copolymer resin: 75.80-88.89%;

[0010] Thermoplastic polyurethane: 9.0-21.3%;

[0011] Inorganic nanomaterials: 0.89-1.95%;

[0012] Formaldehyde absorbent: 0.10-0.12%;

[0013] Antioxidant: 0.29-0.34%;

[0014] Compatibilizer: 0.43-0.68%;

[0015] Lubricant: 0.13-0.15%;

[0016] The above components add up to 100%.

[0017] The copolymer formaldehyde resin is one of the copolymer formaldehyde MC90, M90S, M25S, M270 and other brand products.

[0018] The thermoplastic polyurethane is one of the brands 192, 345, 460, 150, 385, 359, etc.

[0019] The inorganic nano material is one of nano-scale zirconium dioxide, titanium dioxide, silicon dioxide, calcium carbonate, aluminum oxide or montmorillonite, which solves the problem of decreased rigidity caused by increased toughness of polyformaldehyde.

[0020] The formaldehyde absorbent is one of melamine, urea, diethyltriamine, ethylenediamine, dicyandiamide or melamine formal.

[0021] The antioxidant is one of antioxidant 1010, antioxidant 245, antioxidant 1076, antioxidant 20N, antioxidant 1098 or antioxidant 264.

[0022] The compatibilizer is one of ethylene-acrylic acid copolymer (EAA), maleated ethylene-propylene diene monomer rubber (MEPDM), maleic anhydride grafted ethylene-octene copolymer (POE-g-MAH), terminal hydroxyl butadiene-acrylonitrile copolymer (HTBN) or diphenylmethane diisocyanate (MDI).

[0023] The lubricant is one of calcium stearate, zinc stearate, magnesium stearate, ethylene bis stearamide, octadecyl erucamide, and pentaerythritol stearate (PETS).

[0024] The invention also discloses a method for preparing the polyoxymethylene modified material, which comprises the following steps:

[0025] (1) Weighing thermoplastic polyurethane and inorganic nanomaterials, mixing them in a high-speed mixer for 5-15 minutes; pouring the mixture into a feeder after being uniformly mixed, and feeding the mixture to a twin-screw extruder through the feeder for extrusion granulation to obtain a masterbatch;

[0026] (2) the masterbatch obtained above, copolymer formaldehyde resin, antioxidant, lubricant, formaldehyde absorbent, and compatibilizer are placed in a high-speed mixer and mixed for 5-15 minutes; after being uniformly mixed, the mixture is poured into a feeder, and the mixed material is sent to a twin-screw extruder through the feeder for melt blending and extrusion;

[0027] (3) The extruded melt is subjected to wire drawing, cooling, granulation and drying to obtain a polyoxymethylene modified material.

[0028] The head temperature of the twin-screw extruder is controlled at 185-195° C., and the temperature of each section is controlled at 180-190° C.; the main engine speed of the twin-screw extruder is 160-200 rpm, and the feeder speed is 110-150 rpm.

[0029] The beneficial effects of the present invention are:

[0030] (1) The polyoxymethylene modified material prepared by the present invention is an engineering plastic with excellent performance. The modified material has high toughness, high strength, good rigidity and balanced performance.

[0031] (2) The comprehensive performance of the POM modified material in the present invention is good, and the notched impact strength can reach 16.83KJ / m 2 , than POM base material (9.29KJ / m 2) increased by 81.2%, and the nominal strain at break can reach 66%, which is 120% higher than the POM base material (30%), indicating that the notch sensitivity of the modified material is reduced and the toughness is greatly improved. In addition, the bending modulus of the POM modified material can reach 1720MPa, indicating that the rigidity of the modified material is well maintained and a state of rigid-toughness balance is achieved.

[0032] (3) The present invention adds formaldehyde absorbent to POM to reduce the generation and release of irritating gases such as formaldehyde and reduce harm to the human body. In addition, adding antioxidants can improve the processing stability of materials and prevent POM from degrading during processing. Adding compatibilizers can improve the compatibility of POM resin and toughening elastomer and improve the compatibility problem between blending systems.

[0033] (4) The present invention adopts a two-step processing method, which plays a decisive role in the dispersion of nanoparticles in the matrix. Since the core-shell structure particles formed by the elastomer and the nanoparticles can be better dispersed in the POM matrix, the uniformly dispersed core-shell structure plays a role of heterogeneous nucleation, refines the spherulite size, and improves toughness. DETAILED DESCRIPTION

[0034] Example 1

[0035] A polyoxymethylene modified material is prepared from the following raw materials in percentage by weight:

[0036] Copolymer acetal resin M270: 88.89%, thermoplastic polyurethane 192: 9.0%, antioxidant 1010: 0.34%, pentaerythritol stearate: 0.15%, urea: 0.12%, nano zirconium dioxide: 0.89%, ethylene-acrylic acid copolymer (EAA): 0.61%.

[0037] The above components are used to prepare the polyoxymethylene modified material, and the preparation method is as follows:

[0038] (1) Weigh thermoplastic polyurethane 192 and nano zirconium dioxide in proportion, place them in a high-speed mixer and mix them for 5 minutes, pour them into a feeder after mixing evenly, and send the mixed materials to a twin-screw extruder through the feeder for extrusion and granulation to obtain masterbatch. (2) Put the above-obtained masterbatch, copolymer formaldehyde resin M270, antioxidant 1010, pentaerythritol stearate, urea and ethylene-acrylic acid copolymer into a high-speed mixer and mix them for 5 minutes, and send the mixed materials to a twin-screw extruder through a feeder for melt blending and extrusion. (3) The extruded melt strands are subjected to wire drawing, cooling, granulation and drying to obtain polyoxymethylene modified materials. The temperature of each section of the twin-screw extruder is controlled at 180°C, the head temperature is 185°C, the main engine speed of the twin-screw extruder is 160rpm, and the feeder speed is 110rpm. The performance test results of the obtained POM modified materials are shown in Table 1.

[0039] Example 2

[0040] A polyoxymethylene modified material is prepared from the following raw materials in percentage by weight:

[0041] Copolymer acetal resin MC90: 84.76%, thermoplastic polyurethane 345: 12.71%, antioxidant 20N: 0.32%, calcium stearate: 0.15%, diethyltriamine: 0.11%, nano silicon dioxide: 1.27%, terminal hydroxy butadiene-acrylonitrile copolymer (HTBN): 0.68%.

[0042] The above components are used to prepare the polyoxymethylene modified material, and the preparation method is as follows:

[0043] (1) Weigh thermoplastic polyurethane 345 and nano-silicon dioxide in proportion, mix them in a high-speed mixer for 7 minutes, pour them into a feeder after mixing evenly, and send the mixed material to a twin-screw extruder through the feeder for extrusion and granulation to obtain masterbatch. (2) Put the above masterbatch, copolymer formaldehyde resin MC90, antioxidant 20N, calcium stearate, diethyltriamine, and terminal hydroxy butadiene-acrylonitrile copolymer into a high-speed mixer and mix them for 7 minutes, and send the mixed material to a twin-screw extruder through a feeder for melt blending and extrusion. (3) The extruded melt strands are subjected to wire drawing, cooling, granulation, and drying to obtain a polyoxymethylene modified material. The temperature of each section of the twin-screw extruder is controlled at 182°C, the head temperature is 187°C, the main engine speed of the twin-screw extruder is 170rpm, and the feeder speed is 120rpm. The performance test results of the obtained POM modified material are shown in Table 1.

[0044] Example 3

[0045] A polyoxymethylene modified material is prepared from the following raw materials in percentage by weight:

[0046] Copolymer formaldehyde resin MC90: 81.06%, thermoplastic polyurethane 359: 16.2%, antioxidant 245: 0.31%, ethylene bisstearamide: 0.14%, melamine: 0.10%, nano calcium carbonate: 1.62%, diphenylmethane diisocyanate (MDI): 0.57%.

[0047] The above components are used to prepare the polyoxymethylene modified material, and the preparation method is as follows:

[0048] (1) Weigh thermoplastic polyurethane 359 and nano calcium carbonate in proportion, mix them in a high-speed mixer for 10 minutes, pour them into a feeder after mixing evenly, and send the mixed material to a twin-screw extruder through the feeder for extrusion and granulation to obtain masterbatch. (2) Put the above masterbatch, copolymer formaldehyde resin MC90, antioxidant 245, ethylene bis stearamide, melamine, and diphenylmethane diisocyanate into a high-speed mixer and mix them for 10 minutes, and send the mixed material to a twin-screw extruder through a feeder for melt blending and extrusion. (3) The extruded melt strands are subjected to wire drawing, cooling, granulation, and drying to obtain a polyoxymethylene modified material. The temperature of each section of the twin-screw extruder is controlled at 185°C, the head temperature is 190°C, the main engine speed of the twin-screw extruder is 175rpm, and the feeder speed is 125rpm. The performance test results of the obtained POM modified material are shown in Table 1.

[0049] Example 4

[0050] A polyoxymethylene modified material is prepared from the following raw materials in percentage by weight:

[0051] Copolymer formaldehyde resin M90S: 79.0%, thermoplastic polyurethane 460: 18.17%, antioxidant 1076: 0.3%, octadecyl erucamide: 0.14%, dicyandiamide: 0.1%, nano alumina: 1.82%, maleic anhydride grafted ethylene-octene copolymer (POE-g-MAH): 0.47%.

[0052] The above components are used to prepare the polyoxymethylene modified material, and the preparation method is as follows:

[0053] (1) Thermoplastic polyurethane 460 and nano-alumina are weighed in proportion, placed in a high-speed mixer and mixed for 13 minutes, poured into a feeder after being mixed evenly, and the mixed material is sent to a twin-screw extruder through the feeder for extrusion and granulation to obtain a masterbatch. (2) The masterbatch obtained above is mixed with copolymer formaldehyde resin M90S, antioxidant 1076, octadecyl erucic acid amide, dicyandiamide, and maleic anhydride grafted ethylene-octene copolymer, placed in a high-speed mixer and mixed for 13 minutes, and the mixed material is sent to a twin-screw extruder through a feeder for melt blending and extrusion. (3) The extruded melt strand is subjected to wire drawing, cooling, granulation, and drying to obtain a polyoxymethylene modified material. The temperature of each section of the twin-screw extruder is controlled at 187°C, the head temperature is 192°C, the main engine speed of the twin-screw extruder is 180rpm, and the feeder speed is 130rpm. The performance test results of the obtained POM modified material are shown in Table 1.

[0054] Example 5

[0055] A polyoxymethylene modified material is prepared from the following raw materials in percentage by weight:

[0056] Copolymer acetal resin M25S: 77.6%, thermoplastic polyurethane 150: 19.4%, antioxidant 1098: 0.3%, magnesium stearate: 0.14%, melamine formal: 0.1%, nano-montmorillonite: 1.94%, ethylene-acrylic acid copolymer (EAA): 0.47%.

[0057] The above components are used to prepare the polyoxymethylene modified material, and the preparation method is as follows:

[0058] (1) Weigh thermoplastic polyurethane 150 and nano-montmorillonite in proportion, mix them in a high-speed mixer for 13 minutes, pour them into a feeder after mixing evenly, and send the mixed material to a twin-screw extruder through the feeder for extrusion and granulation to obtain masterbatch. (2) Put the above masterbatch, copolymer formaldehyde resin M25S, antioxidant 1098, magnesium stearate, melamine formal, and ethylene-acrylic acid copolymer into a high-speed mixer and mix them for 13 minutes, and send the mixed material to a twin-screw extruder through a feeder for melt blending and extrusion. (3) The extruded melt strands are subjected to wire drawing, cooling, granulation, and drying to obtain a polyoxymethylene modified material. The temperature of each section of the twin-screw extruder is controlled at 190°C, the head temperature is 195°C, the main engine speed of the twin-screw extruder is 190rpm, and the feeder speed is 140rpm. The performance test results of the obtained POM modified material are shown in Table 1.

[0059] Example 6

[0060] A polyoxymethylene modified material is prepared from the following raw materials in percentage by weight:

[0061] Copolymer acetal resin M270: 75.80%, thermoplastic polyurethane 385: 21.3%, antioxidant 264: 0.29%, zinc stearate: 0.13%, ethylenediamine: 0.1%, nano titanium dioxide: 1.95%, maleated ethylene propylene diene monomer (MEPDM): 0.43%.

[0062] The above components are used to prepare the polyoxymethylene modified material, and the preparation method is as follows:

[0063] (1) Weigh thermoplastic polyurethane 385 and nano titanium dioxide in proportion, place them in a high-speed mixer and mix them for 15 minutes. After mixing evenly, pour them into a feeder, and send the mixed material to a twin-screw extruder through the feeder for extrusion and granulation to obtain a masterbatch. (2) The masterbatch obtained above, copolymer formaldehyde resin M270, antioxidant 264, zinc stearate, ethylenediamine, and maleated ethylene propylene rubber are placed in a high-speed mixer and mixed for 15 minutes, and the mixed material is sent to a twin-screw extruder through a feeder for melt blending and extrusion. (3) The extruded melt strands are subjected to wire drawing, cooling, granulation, and drying to obtain a polyoxymethylene modified material. The temperature of each section of the twin-screw extruder is controlled at 190°C, the head temperature is 195°C, the main engine speed of the twin-screw extruder is 200rpm, and the feeder speed is 150rpm. The performance test results of the POM modified material are shown in Table 1.

[0064] Table 1 Performance test results of Examples 1 to 6

[0065]

[0066] It can be seen from the examples that the POM modified material of the present invention has good comprehensive performance, and the notched impact strength can reach 16.83KJ / m 2 , than POM base material (9.29KJ / m 2 ) increased by 81.2%, and the nominal strain at fracture can reach 66%, which is 120% higher than that of POM base material (30%), indicating that the notch sensitivity of the modified material is reduced and the toughness is greatly improved.

[0067] The technical solutions disclosed and proposed by the present invention can be realized by those skilled in the art by referring to the contents of this article and appropriately changing the conditions, routes and other links. Although the methods and preparation techniques of the present invention have been described through preferred embodiments, relevant technicians can obviously modify or re-combine the methods and technical routes described herein without departing from the content, spirit and scope of the present invention to realize the final preparation technology. It should be particularly noted that all similar substitutions and modifications are obvious to those skilled in the art, and they are all considered to be included in the spirit, scope and content of the present invention.

Claims

1. A polyoxymethylene modified material, characterized in that: Includes the following components and mass percentage content: Acetal copolymer resin: 75.80-88.89%; Thermoplastic polyurethane: 9.0-21.3%; Inorganic nanomaterials: 0.89-1.95%; Formaldehyde absorbent: 0.10-0.12%; Antioxidant: 0.29-0.34%; Compatibilizer: 0.43-0.68%; Lubricant: 0.13-0.15%; The above components add up to 100%.

2. The polyoxymethylene modified material according to claim 1, characterized in that: The copolymer acetal resin is one of the copolymer acetal brands MC90, M90S, M25S or M270.

3. The polyoxymethylene modified material according to claim 1, characterized in that: The thermoplastic polyurethane is one of the 192, 345, 460, 150, 385 or 359 brands.

4. The polyoxymethylene modified material according to claim 1, characterized in that: The inorganic nanomaterial is one of nano-scale zirconium dioxide, titanium dioxide, silicon dioxide, calcium carbonate, aluminum oxide or montmorillonite.

5. The polyoxymethylene modified material according to claim 1, characterized in that: The formaldehyde absorbent is one of melamine, urea, diethyltriamine, ethylenediamine, dicyandiamide or melamine formal.

6. The polyoxymethylene modified material according to claim 1, characterized in that: The antioxidant is one of antioxidant 1010, antioxidant 245, antioxidant 1076, antioxidant 20N, antioxidant 1098 or antioxidant 264.

7. The polyoxymethylene modified material according to claim 1, characterized in that: The compatibilizer is one of ethylene-acrylic acid copolymer, maleic anhydride ethylene-propylene rubber, maleic anhydride grafted ethylene-octene copolymer, terminal hydroxyl butadiene-acrylonitrile copolymer or diphenylmethane diisocyanate.

8. The polyoxymethylene modified material according to claim 1, characterized in that: The lubricant is one of calcium stearate, zinc stearate, magnesium stearate, ethylene bis stearamide, octadecyl erucamide or pentaerythritol stearate.

9. The method for preparing the polyoxymethylene modified material according to claim 1, characterized in that: The following steps are involved: (1) Weighing thermoplastic polyurethane and inorganic nanomaterials, mixing them in a high-speed mixer for 5-15 minutes; pouring the mixture into a feeder after being uniformly mixed, and feeding the mixture to a twin-screw extruder through the feeder for extrusion granulation to obtain a masterbatch; (2) the masterbatch obtained above, copolymer formaldehyde resin, antioxidant, lubricant, formaldehyde absorbent, and compatibilizer are placed in a high-speed mixer and mixed for 5-15 minutes; after being uniformly mixed, the mixture is poured into a feeder, and the mixed material is sent to a twin-screw extruder through the feeder for melt blending and extrusion; (3) The extruded melt is subjected to wire drawing, cooling, granulation and drying to obtain a polyoxymethylene modified material.

10. The method for preparing the polyoxymethylene modified material according to claim 9, characterized in that: The head temperature of the twin-screw extruder is controlled at 185-195° C., and the temperature of each section is controlled at 180-190° C.; the main engine speed of the twin-screw extruder is 160-200 rpm, and the feeder speed is 110-150 rpm.

Citation Information

Patent Citations

  • Polyoxymethylene / thermoplastic polyurethane / amorphous thermoplastic polymer blends

    CN1027511C

  • Modified polyformaldehyde material toughened and reinforced by polyurethane resin (PUR) and preparation method thereof

    CN111253708A

  • Polyformaldehyde / thermoplastic polyurethane elastomer blends and their preparation process and use

    CN1233733C

  • Polyoxymethylene composite resin composition and articles prepared therefrom

    CN1283719C

Cited By

  • POM (polyoxymethylene) composite material as well as preparation method and application thereof

    CN121319546A